What influences nurses' practice towards enteral nutrition support in the intensive care units? - Ambaye Dejen Tilahun; Bikis liyew; Tilahun Kassew (Elsevier, 2024)
Background: Enteral nutrition is crucial for critically ill patients to maintain gastrointestinal function, reduce complications, shorten the length of stay, and enhance wound healing. Nurses are essential in carrying out nutritional care and promoting the early commencement of enteral nutrition. Objective: To assess practice and barriers towards enteral nutritional support for critically ill patients among nurses working in intensive care units. Methods: Institution-based cross-sectional study with a total of 264 nurses were recruited by convenience sampling technique. Data were collected using a Structured and pretested self-administered questionnaire entered by using epi-info 7.2.2 and analyzed by using STATA 14. Descriptive and inferential statistics were used to summarize the data distribution. Simple and multiple linear regression analyses were employed. Adjusted unstandardized beta (β) coefficient at 95 % Confidence interval was used at p-value < 0.05. Result: The mean score of practice towards enteral nutritional supports was 6.36 ± 3.16 [95 % CI (5.99, 6.76)]. Having training (β = 3.23, 95 % CI: 2.39, 4.07), knowledge (β = 0.13, 95 % CI: 0.07, 0.18), attitude (β = 0.04, 95 % CI: 0.02, 0.07), intensive care units' resources subscale (β = -0.24, 95 %CI: −0.02, −0.44), and critical care provider attitude and behavior subscale (β = -0.22, 95 % CI: −0.10, −0.33) were found significant factors of practice towards enteral nutritional support. Conclusion: Nurses' approach to enteral nutrition support was significantly substandard, and guidelines and resources for the provision of nutritional support are not readily accessible. Targeted nutrition-related training programs, and addressing intensive care provider attitudes and behaviors are crucial in promoting better practices related to enteral nutrition support.